Study on the hydrothermal effect in ice materials under the polar glacier runway dynamic load - Zhiyuan Wang; Shengrong Zhang; Ze Zhang; Chunlei Xie; Kunchao Zhou; Mingyang Yuan (Case Studies in Construction Materials)
The problem of ice transportation during the polar scientific expedition is very important. In order to provide a research basis for the glacier runway in the polar region, this paper approximates the load generated by the aircraft running on the glacier runway as a dynamic load, and uses the ambient temperature and load frequency as test variables to study the variation of temperature and moisture in the ice under dynamic load. The results show that due to the influence of dynamic load, the ice test sample has the phenomenon of alternating competition between the temperature rise stage and the temperature drop stage, and there is a temperature difference at different depths of the test sample. In the two groups of B and C with slower load frequency, the amount of water migration mainly changes with the temperature change in the test sample. In the group A test with faster load frequency, it was found that the temperature fluctuation was small during the test, but the amount of water migration increased. Finally, the experimental results are discussed from the perspective of hydrogen bond compression relaxation of the basic unit (O:H-O) composed of ice and water.